Pengaruh Gaya Kepemimpinan, Motivasi Kerja, Disiplin Kerja, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Bank Muamalat Kota Surakarta - Wijaya, Fajar; , Sri Murwanti,S.E.,M.M (2016)
This study aims to determine the effect of leadership, motivation, work discipline and work environment to employees performance at PT. Bank Muamalat Surakarta. This study uses the survey design, the research took this sample of employees at PT. Bank Muamalat Surakarta. The analysis tool used validity and reliability test, classic assumption test and multiple linear regression analysis. The findings showed that motivation, leadership style, work discipline and the work environment either simultaneously or partially significant effect on employee performance.